Disparities in eating disorder risk and diagnosis among sexual minority college students: Findings from the national Healthy Minds Study. Issue 9 (25th May 2020) - Hazzard, Vivienne M.; Simone, Melissa; Borg, Skylar L.; Borton, Kelley A.; Sonneville, Kendrin R.; Calzo, Jerel P.; Lipson, Sarah K.
Abstract: Objective: To examine differences in eating disorder (ED) risk and diagnosis by sexual orientation in a national sample of college students. Method: Data from 178 U.S. colleges and universities participating in the Healthy Minds Study between 2016 and 2019 were analyzed (36, 691 cisgender men, 81, 730 cisgender women; 15.7% self‐identifying as sexual minorities). Outcomes were ED risk (≥2 on the SCOFF) and self‐reported lifetime ED diagnosis. Prevalence estimates adjusted for demographics and weight status were computed via logistic regression. Results: Higher proportions of questioning (29.1%), bisexual (26.3%), and gay men (30.9%) exhibited elevated risk than heterosexual men (14.3%), and a higher proportion of gay men exhibited elevated risk than bisexual men. Higher proportions of questioning (34.5%) and bisexual women (34.6%) exhibited elevated risk than heterosexual women (27.6%); proportions of lesbian (28.1%) and heterosexual women were similar. Among those with elevated risk, higher proportions of bisexual (5.0%) and gay men (7.1%) and of questioning (14.7%), bisexual (18.1%), and lesbian women (19.6%) had been diagnosed relative to heterosexual men (2.0%) and heterosexual women (10.3%), respectively. Discussion: Questioning and bisexual individuals appear to be particularly vulnerable; they may experience elevated ED risk relative to their heterosexual peers yet underdiagnosis relative to their gay or lesbian peers.